Nutrient composition and in vitro ruminal degradability of selected local plants used as goat feed in Malaysia - Abdul Ghani, Ahmad Afifi; Shahudin, Muhammad Syafiq; Saad, Mohd Zamri; Abu Bakar @ Zakaria, Md Zuki; Haron, Abd Wahid; Kasim, Azhar; Salisi, Mohd Shahrom; Abu Hassim, Hasliza (2015)
A comparative study of nutrient composition and in vitro ruminal degradability of selected local plants (Macaranga sp. and Mallotus sp.) and Napier grass (Pennisetum purpureum) used as goat feed were carried out. Napier grass was used as a control group as it is common and widely been used (e. gfibre source) in goats diet. All plants were analyzed for nutrient composition by proximate analysis (dry matter; crude protein; crude fibre; crude fat) and in vitro ruminal degradability was performed to determine the total gas andvolatile fatty acids (acetate; propionate; butyrate) production. The result obtained from proximate analysis revealed that there were significant difference (P<0.05) of all nutrient composition for each local plant species against Napier grass. Dry matter content was highest in Macaranga sp. (50.92%) followed by Mallotus sp. (45.41%) and Napier grass (13.04%). Crude protein was highest in Macaranga sp. (7.18%) followed by Mallotussp. (6.78%) and Napier grass (3.88%). Mallotussp.has the highest crude fat content (5.22%) followed by Macaranga sp. (4.85%) and Napier grass (2.84%). As for crude fibre content, Napier grass showed the highest content (25.38%) followed by Mallotus sp. (15.47%) and Macaranga sp. (12.00%). For the in vitro ruminal degradability, the highest total gas production was shown by Napier grass (31.00ml), followed by Macaranga sp. (28.67ml) and Mallotus sp. (23.33ml). Acetate production was highest in Mallotus sp. (733.49mM/ml) followed by Napier grass (605.61mM/ml) and Macaranga sp. (599.85mm/ml) whereas propionate production was highest in Mallotus sp. (28.61mM/ml) followed by Napier grass (24.45mM/ml) and Macaranga sp. (24.23mM/ml).As for butyrate production, Napier grass showed the highest value (11.26mM/ml), followed by Macaranga sp. (11.19mm/ml) and Mallotus sp. (10.36mM/ml). However, there was no significant difference shown for acetate, propionate and butyrate production between all samples. Thus, based on the nutrient composition and in vitro ruminal degradability findings, it shows that these local plants could be used as a good feed source for goats. In addition, a proper feeding regime using these local plants need to be considered in order to ensure a balance diet for the goats.